Analisis dan Implementasi Network Ad-blocking Pi-Hole di Raspberry Pi 4 Menggunakan OPNSense DHCP Dengan Metode PPDIOO Studi Kasus Dinas Komunikasi Informatika Statistik dan Persandian Kabupaten Lebak - Muhamad Apriyatna (CV. Multi Kreasi Media, 2022)
In the development of technology, especially the presence of advertising media as one of the attractions of potential buyers. However, everything is irrelevant if the user sees it even gets annoyed because it eats up extra data that is excessive with the number of ads on the web page. Therefore, we need a system with the ability to filter advertisements on web pages and make it seem as if local DNS is the only data connection stream with the Unbound DNS tools in OPNSense. Local DNS built based on the Pi-Hole system installed into the Raspberry Pi to filter data or advertisements. In addition, the extra security with OPNSense makes it a DNS resolver for the flow of data connections. Along with that, the implementation of Pi-Hole in the Raspberry Pi by utilizing DHCP OPNSense has succeeded in filtering advertisements and cutting extra data in network security to provide additional protection. By implementing the Pi-Hole on the Raspberry Pi by utilizing DHCP OPNSense, it aims to provide a solution other than maintaining network security so that the development of this system can run efficiently. The system development applies the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) method because this model is very suitable and easy to develop and design a system.